Sport or school? Dreams and dilemmas for talented young Danish football players - Krogh Christensen, M.; Kahr Sørensen, J. (European Physical Education Review, 2009)
Today`s young semi-professional football players are expected to continue their education while honing their talents as footballers. This means they must balance the contradictory demands that come from their education establishments and their football clubs. The present study explores how young Danish male football talents experience and describe these different forces in their life space (Lewin, 1951). Data for the study are gathered using a narrative and qualitative approach, including four focus group interviews with 25 footballers aged 15—19, followed by individual qualitative interviews with eight of the footballers. The elite football culture has an almost magnetic attraction for the young footballers in the study. Even if the espoused value (Schein, 1990) of a good set of academic qualifications does not entirely measure up to this, the insistence from the outside world on the importance of completing one`s education is manifest and associated with significant personal concerns, lower examinations results, stress, drop-out and mental breakdown.